Exploring the Relationship Between Paternalistic Leadership, Teacher Commitment, and Job Satisfaction in Chinese Schools - Shi, Xiao; Yu, Zeyuan; Zheng, Xin (Frontiers in Psychology, 2020)
Paternalistic leadership is prevalent in organizations in East Asia, but few studies have examined its potential effects in school contexts. This study explored the relationship between paternalistic leadership, trust in the principal and teachers’ satisfaction and commitment to students, with a focus on the mediating role of trust in the principal in Chinese schools. Using a quantitative method, the study investigated 408 primary schoolteachers in mainland China. The results showed that the three dimensions of paternalistic leadership had different effects on teachers’ job satisfaction, trust in the principal and commitment to students. Moral leadership had positive effects, while authoritarian leadership had negative effects on teachers’ job satisfaction and commitment to students. Meanwhile, trust in the principal played a mediating role of authoritarian and moral leadership on teachers’ job satisfaction and commitment to students. Finally, implications and suggestions are discussed for leadership practices in Chinese schools and those in similar cultures.